Complete genome sequences of five bacteria isolated from rice plants in a paddy field in Sekinchan, Selangor, Malaysia - Abdul Malek, Ahmad Zuhairi; Mohd Hashim, Amalia; Khairil Mokhtar, Nur Fadhilah; Saidi, Noor Baity; Abu Bakar, Mohd Faizal; Singaram, Nallamai (American Society for Microbiology, 2024)
This study examines the genome sequences of five endophytic bacterial isolates from the Oryza sativa microbiome to assess their potential as plant bio-inoculants. The five complete bacterial genomes from the genera Pseudomonas, Burkholderia, Sphingobacterium, Stenotrophomonas, and Pantoea were sequenced using Nanopore long-read sequencing technology.